2023
DOI: 10.3390/s23115099
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Phyllodes Tumors and Fibroadenomas through Breast Ultrasound: Deep-Learning Model Outperforms Ultrasound Physicians

Abstract: The preoperative differentiation of breast phyllodes tumors (PTs) from fibroadenomas (FAs) plays a critical role in identifying an appropriate surgical treatment. Although several imaging modalities are available, reliable differentiation between PT and FA remains a great challenge for radiologists in clinical work. Artificial intelligence (AI)-assisted diagnosis has shown promise in distinguishing PT from FA. However, a very small sample size was adopted in previous studies. In this work, we retrospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Research data have shown that in the accurate diagnosis of breast cancer, the accuracy of deep learning model in diagnosing malignant tumours in BI-RADS 4a patients is 92.86%, which theoretically reduces unnecessary biopsies by 67.86% [ 29 ], increasing diagnosticity while significantly reducing invasive operations for patients. In another study using a deep learning model of ultrasound images to discriminate breast fibroadenomas from lobular breast tumors, the AUC value reached 0.91 [ 30 ]. Therefore, the combined application of multimodal ultrasound technology has a broad application prospect for the diagnosis and prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Research data have shown that in the accurate diagnosis of breast cancer, the accuracy of deep learning model in diagnosing malignant tumours in BI-RADS 4a patients is 92.86%, which theoretically reduces unnecessary biopsies by 67.86% [ 29 ], increasing diagnosticity while significantly reducing invasive operations for patients. In another study using a deep learning model of ultrasound images to discriminate breast fibroadenomas from lobular breast tumors, the AUC value reached 0.91 [ 30 ]. Therefore, the combined application of multimodal ultrasound technology has a broad application prospect for the diagnosis and prognosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%